6x+2x-5=43

Simple and best practice solution for 6x+2x-5=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2x-5=43 equation:


Simplifying
6x + 2x + -5 = 43

Reorder the terms:
-5 + 6x + 2x = 43

Combine like terms: 6x + 2x = 8x
-5 + 8x = 43

Solving
-5 + 8x = 43

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 8x = 43 + 5

Combine like terms: -5 + 5 = 0
0 + 8x = 43 + 5
8x = 43 + 5

Combine like terms: 43 + 5 = 48
8x = 48

Divide each side by '8'.
x = 6

Simplifying
x = 6

See similar equations:

| (X-3)(X+3)=6x^2-14 | | 5+3(4x-2)=-18 | | a+7=11 | | 16R+4R+80=X | | -2x^4(6x^3-5x+5)= | | 790=7.5x+(197.5+(-1.875x)) | | 9+2(b-8)=9(-3-2b) | | 5p=16-3p | | 6-x+2x=3x | | 3(6y-6)-(2y+7)= | | 1.5=x*11 | | 5e-14=8 | | 4n(-n^3-4n+1)= | | 8-2(2x-5)=6 | | -24+w-8=4 | | 3z-2z=8 | | 3x^2-2x=5x+1 | | 7x^2+5x-16=0 | | -750+150(3)= | | 5x-1=2(x+10) | | 17y-2418=59 | | -750+150(2)= | | -5.6h+72=-30 | | -21=-5x+3x+1 | | 6a(7a^2+8a-5)= | | 35x^2-13x-4=0 | | x*25=10 | | (2y+4)(y+7)=0 | | 3(6x-6)-(2x+7)= | | 4=m | | 5-.33333x=17 | | 2784=(40+2x)(30+2x) |

Equations solver categories